2006
DOI: 10.1073/pnas.0605873103
|View full text |Cite
|
Sign up to set email alerts
|

Silencing leaf sorbitol synthesis alters long-distance partitioning and apple fruit quality

Abstract: Sorbitol and sucrose are major products of photosynthesis distributed in apple trees (Malus domestica Borkh. cv. ''Greensleeves'') that affect quality in fruit. Transgenic apple plants were silenced or up-regulated for sorbitol-6-phosphate dehydrogenase by using the CaMV35S promoter to define the role of sorbitol distribution in fruit development. Transgenic plants with suppressed sorbitol-6-phosphate dehydrogenase compensated by accumulating sucrose and starch in leaves, and morning and midday net carbon assi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
93
1
1

Year Published

2007
2007
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 126 publications
(102 citation statements)
references
References 48 publications
(25 reference statements)
7
93
1
1
Order By: Relevance
“…Transgenic apples containing the introduced antisense S6PDH gene decreased S6PDH activity, but did not influence SPS activity, but increased fructose 1,6-bisphosphatase activity (Cheng et al, 2005). Similar transgenic apples reduced SDH activity in fruit, but did not influence the activities of AIV, fructokinase or hexokinase (Teo et al, 2006). Such transgenic apples reduced sorbitol synthesis and SDH activity in the shoot tip, but did not influence AIV activity, and increased SuSy activity (Zhou et al, 2006).…”
Section: Phenotypic Expression By Regulating Expression Of Sucrose-anmentioning
confidence: 95%
“…Transgenic apples containing the introduced antisense S6PDH gene decreased S6PDH activity, but did not influence SPS activity, but increased fructose 1,6-bisphosphatase activity (Cheng et al, 2005). Similar transgenic apples reduced SDH activity in fruit, but did not influence the activities of AIV, fructokinase or hexokinase (Teo et al, 2006). Such transgenic apples reduced sorbitol synthesis and SDH activity in the shoot tip, but did not influence AIV activity, and increased SuSy activity (Zhou et al, 2006).…”
Section: Phenotypic Expression By Regulating Expression Of Sucrose-anmentioning
confidence: 95%
“…This increase in Brix value and decrease in acidity favor high fruit quality. Kanamaru et al (2004) and Teo et al (2006) examined apple vegetative growth and found some inhibition after suppression of S6PDH expression and promotion after overexpression of S6PDH, suggesting that sorbitol is a favorable photosynthate for apple vegetative growth.…”
Section: ) Sorbitol 6-phosphate Dehydrogenase (S6pdh)mentioning
confidence: 99%
“…Cheng et al (2005) further showed that starch is also increased in transgenic apple plants with suppressed expression of S6PDH. Fruit from apples transformed with S6PDH cDNA was analyzed by Teo et al (2006), who found that although fruit weight and firmness did not change, there was an increase in glucose and a decrease in malate content after suppression of S6PDH expression. This increase in Brix value and decrease in acidity favor high fruit quality.…”
Section: ) Sorbitol 6-phosphate Dehydrogenase (S6pdh)mentioning
confidence: 99%
“…According to these reports, it is possible to produce transgenic hypoallergenic apples using RNAi. Research on leaf sorbitol silencing suggests that sorbitol distribution affects fruit quality such as starch accumulation and sugar-acid balance (Teo et al, 2006). In Citrus, the down regulation of putative thermostable pectin methylesterase genes is projected as a possible solution for the undesirable separation of juice into clear serum and particulate phase (Guo et al, 2005).…”
Section: Gene Silencing and Wood Quality Fruit Quality And Other Traitsmentioning
confidence: 99%
“…(Jouanin et al, 2000;Kumar & Fladung, 2001;Hawkins et al, 2003), Solanum dulcamara L. (Curtis et al, 2000), Malus domestica Borkh. (Ko et al, 1998;Dandekar et al, 2004;Viss et al, 2003;Broothaerts et al, 2004;Gilissen et al, 2005;Teo et al, 2006), Pinus radiata D. Don. (Moller et al, 2005;Tang et al, 2005a;2005b;Wagner et al, 2005;Tang et al, 2006), Juglans regia L. (Escobar et al, 2002), Coffea canephora (Ogita et al, 2003), Eucalyptus sp.…”
Section: Applications Of Gene Silencing In Woody Plantsmentioning
confidence: 99%